On the Dissociation of Word/Nonword Repetition Effects in Lexical Decision: An Evidence Accumulation Account - Perea, Manuel; Marcet, Ana; Vergara-Martínez, Marta; Gomez, Pablo (Frontiers in Psychology, 2016)
A number of models of visual-word recognition assume that the repetition of an item in a lexical decision experiment increases that item’s familiarity/wordness. This would produce not only a facilitative repetition effect for words, but also an inhibitory effect for nonwords (i.e., more familiarity/wordness makes the negative decision slower). We conducted a two-block lexical decision experiment to examine word/nonword repetition effects in the framework of a leading “familiarity/wordness” model of the lexical decision task, namely, the diffusion model (Ratcliff et al., 2004). Results showed that while repeated words were responded to faster than the unrepeated words, repeated nonwords were responded to more slowly than the nonrepeated nonwords. Fits from the diffusion model revealed that the repetition effect for words/nonwords was mainly due to differences in the familiarity/wordness (drift rate) parameter. This word/nonword dissociation favors those accounts that posit that the previous presentation of an item increases its degree of familiarity/wordness.